Long-term outcome after haploidentical stem cell transplant and infusion of T cells expressing the inducible caspase 9 safety transgene - Zhou, Xiaoou (American Society of Hematology, 2014)
Adoptive transfer of donor-derived T lymphocytes expressing a safety switch may promote immune reconstitution in patients undergoing haploidentical hematopoietic stem cell transplant (haplo-HSCT) without the risk for uncontrolled graft versus host disease (GvHD). Thus, patients who develop GvHD after infusion of allodepleted donor-derived T cells expressing an inducible human caspase 9 (iC9) had their disease effectively controlled by a single administration of a small-molecule drug (AP1903) that dimerizes and activates the iC9 transgene. We now report the long-term follow-up of 10 patients infused with such safety switch-modified T cells. We find long-term persistence of iC9-modified (iC9-T) T cells in vivo in the absence of emerging oligoclonality and a robust immunologic benefit, mediated initially by the infused cells themselves and subsequently by an apparently accelerated reconstitution of endogenous naive T lymphocytes. As a consequence, these patients have immediate and sustained protection from major pathogens, including cytomegalovirus, adenovirus, BK virus, and Epstein-Barr virus in the absence of acute or chronic GvHD, supporting the beneficial effects of this approach to immune reconstitution after haplo-HSCT. This study was registered at www.clinicaltrials.gov as #NCT00710892.